2018
DOI: 10.1111/ijn.12650
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sleep hygiene education and relaxation exercises on insomnia among postmenopausal women: A randomized clinical trial

Abstract: The findings of study suggest that nurses teaching progressive relaxation exercises and sleep hygiene would benefit postmenopausal women who suffer from insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 39 publications
3
26
0
2
Order By: Relevance
“…En cuanto a las fortalezas del presente estudio, destacaremos que la muestra era homogénea y con unas particularidades muy concretas, ya que el perfil de la mujer en la etapa posmenopáusica resulta muy diferente al de otras fases de la vida y en él se hacen patentes riesgos para la salud que necesitan estudiarse en profundidad (40).…”
Section: Discussionunclassified
“…En cuanto a las fortalezas del presente estudio, destacaremos que la muestra era homogénea y con unas particularidades muy concretas, ya que el perfil de la mujer en la etapa posmenopáusica resulta muy diferente al de otras fases de la vida y en él se hacen patentes riesgos para la salud que necesitan estudiarse en profundidad (40).…”
Section: Discussionunclassified
“…Measures aimed at sleep hygiene, progressive relaxation and the promotion of comfort may be prescribed by nurses to improve sleep quality. 16 Another frequent problem among women was "financial difficulty", a risk factor associated with the risk of feeling helpless, signaled as worrying by the women surveyed, which can greatly affect women's health.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there were varying levels of clarity about whether formal comparisons between intervention and control groups had been made. In several studies, authors reported that no adverse events had occurred or that none were reported during the study [21,31,39,[41][42][43][44][45][46][47][48]. Although it is possible that this represents a rate of zero in each trial arm, it is difficult to be sure when there is no specific reference to the separate groups.…”
Section: Question 5 Rates Of Adverse Events In Cbtimentioning
confidence: 99%